Evaluation of Technology and Design Course 2018 Curriculum According to Teachers' Views - Mehmet Aydın Sağlık; Çiğdem Aldan Karademir (Anı Publishing, 2019)
The aim of this research is to reveal the views of the teachers towards the 2018 Technology and Design course curriculum. This research was designed as a qualitative research, and conducted with twelve teachers working in a city of Mediterranean Region. The study group of study was determined according to the maximum diversity sample. Semi-structured interview form developed by researchers was used in in-depth interviews with Technology and Design teachers. The obtained data was separated into the themes and codes by using content analysis from qualitative data analysis techniques. Teachers' views on the Technology and Design curriculum are interpreted in the context of findings. According to thefindings, teachers find the program positive in terms of learning areas, content, effect on student creativity and student level. However, they were negative in terms of measurement and evaluation.It is also seen that there are shortcomings in the weekly course hours, workshop equipment and teacher in-service training points.